Efektivitas Media Lembar Balik Terhadap Tingkat Pengetahuan dan Sikap Ibu dalam Pemberian MP-ASI - Hasanah, Devi Miftahul; Lesmana, Hendy (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Toddlers in the developing phase of growth and development are more susceptible to health issues arising from dietary deficiencies. Optimal nutrition during the early stages of life significantly influences the child's physical, cognitive, and social development. Parental variables associated with nutritional issues in toddlers encompass parental education and occupation and mother knowledge, attitudes, and behavior about nutrition. To enhance maternal knowledge, it is necessary to develop health education programs that promote awareness and understanding of health requirements. This will facilitate the adoption of healthy behaviors. This study aims to assess the efficacy of flip-sheet media in enhancing the knowledge and attitudes of mothers in delivering weaning food. The research approach employed in this study is quantitative, utilizing a Quasi-Experimental design with a post-test-only Control Group Design. The sample size for this study consisted of 64 moms with children between the ages of 6 and 24 months. The research consisted of a total sample size of 55 respondents, selected using the Purposive Sampling approach. The Mann-Whitney U test was employed to evaluate the data. This study demonstrates a notable correlation between the knowledge and attitude of mothers in providing weaning food through a flip sheet medium. Future researchers should conduct comparative studies between one health promotion medium and other media. Keywords: Flip-sheets,  Weaning Food, Health Education, Mother’s Knowledge and Attitudes  ABSTRAK Balita berada pada masa awal pertumbuhan dan perkembangan, maka mereka sangat rentan mengalami gangguan kesehatan akibat masalah gizi. Awal gizi yang baik akan sangat berakibat pada kehidupan yaitu pada perkembangan fisik, kognitif dan sosial anak. Faktor orang tua yang berhubungan dengan masalah gizi pada balita, antara lain pendidikan dan pekerjaan orang tua, serta pengetahuan, sikap, dan perilaku ibu tentang gizi. Upaya untuk meningkatkan pengetahuan ibu perlu dilaksanakan penyuluhan kesehatan untuk meningkatkan pengetahuan dan sikap tentang kebutuhan kesehatan agar mudah terjadinya perilaku sehat. Tujuan penelitian ini adalah menganalisis efektivitas media lembar balik terhadap tingkat pengetahuan dan sikap ibu dalam pemberian MP-ASI. Metode penelitian ini adalah kuantitatif dengan desain Quasi Experimental dengan Post Test Only Control Group Design. Populasi dalam penelitian ini sebanyak 64 ibu yang memiliki balita usia 6-24 bulan. Jumlah sampel penelitian ini adalah 55 responden yang dipilih menggunakan teknik Purposive Sampling. Data dianalisis dengan uji Mann Whitney U. Berdasarkan hasil penelitian ini menunjukkan ada pengaruh yang signifikan antara pengetahuan dan sikap ibu dalam pemberian MP-ASI terhadap media lembar balik. Peneliti selanjutnya direkomendasikan untuk membandingkan salah satu media promosi kesehatan dengan media lainnya. Kata Kunci: Lembar Balik, MP-ASI, Pendidikan Kesehatan, Pengetahuan dan Sikap Ibu